Getting a Seat at the Table: Changes in Military Participation in Government and Coups - Peter B White (Research & Politics)
Why do coups happen and how can state leaders affect their likelihood? Existing research focuses on structural factors as well as “coup-proofing” as drivers of coup risk. I argue that the literature misses an important alternative avenue by which leaders affect the likelihood that their militaries remove them from office: adding or removing military officers from the government. When leaders bring military officers into the government, they signal to the military that there is a peaceful path to sharing power and provide an alternative to coups. In contrast, removing military officers from government dramatically increases the risk of a coup attempt as the military retaliates against the leader’s power grab. I test this theory using cross-national data that captures changes in military representation in national cabinets and state councils from 1969 to 2008 and find mixed support. In line with the theory, there is strong evidence that large reductions in the military’s government positions lead to coup attempts, and more modest evidence that large increases reduce coup attempts. However, contrary to expectations, the results also suggest that small increases in military government positions increase the risk of a coup.